2009
DOI: 10.1007/s12526-009-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

A new, disjunct species of Speleonectes (Remipedia, Crustacea) from the Canary Islands

Abstract: We describe Speleonectes atlantida n. sp. as the third species of Remipedia that was found outside the main distribution area of this group in the Caribbean region. S. atlantida was collected by cave divers equipped with closed circuit rebreathers from the far interior of the Túnel de la Atlántida, an anchialine volcanic lava tube, on the Canarian island of Lanzarote. The new species occurs in sympatry with S. ondinae, to which it is morphologically closely related. S. atlantida can be distinguished from S. on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Speleophriopsis scottodicarloi from Bermuda is the sister species of the eastern pairing of S. balearicus and S. canariensis, similarly Boxshallia from Lanzarote in the Canaries and Mexicophria n. gen. from Mexico are sister taxa, as are Speleophria gymnesica from Majorca and S. bivexilla from Bermuda. Similar amphiatlantic distribution patterns have been found in a range of other cave crustacean taxa including ostracods, amphipods and remipedes (Kornicker et al 2007, Bauzà-Ribot et al 2012, Koenemann et al 2009. A vicariance-based explanation has been proposed to explain such distributions: namely that such amphiatlantic sister taxa were separated by the opening of the proto-Atlantic ocean in the later Mesozoic (e.g.…”
Section: Discussionsupporting
confidence: 53%
“…Speleophriopsis scottodicarloi from Bermuda is the sister species of the eastern pairing of S. balearicus and S. canariensis, similarly Boxshallia from Lanzarote in the Canaries and Mexicophria n. gen. from Mexico are sister taxa, as are Speleophria gymnesica from Majorca and S. bivexilla from Bermuda. Similar amphiatlantic distribution patterns have been found in a range of other cave crustacean taxa including ostracods, amphipods and remipedes (Kornicker et al 2007, Bauzà-Ribot et al 2012, Koenemann et al 2009. A vicariance-based explanation has been proposed to explain such distributions: namely that such amphiatlantic sister taxa were separated by the opening of the proto-Atlantic ocean in the later Mesozoic (e.g.…”
Section: Discussionsupporting
confidence: 53%
“…Island of Lanzarote, but still significantly larger than the intraspecific genetic distance of ~0.5% within five remipede species reported by Koenemann et al (2009), and, even more importantly, larger than the genetic distance between various populations of X. tulumensis ranging from 0.4% to 1.2% (Neiber et al 2012) (see also Table 2). The intraspecific genetic distance within X. cozumelensis based on three individuals examined in this study varied between 0-3% (Table 2).…”
Section: Olesen J Et Al a New Species Of Remipedia And Phylogeny Omentioning
confidence: 80%
“…Characteristics such as their cephalic anatomy warranted their classification in the subphylum Crustacea (Yager, 1981), which was later confirmed by molecular studies (von Reumont et al, 2012). Remipedes follow similar distribution patterns to those of halocyprid ostracods (Kornicker et al, 2007), and can be found exclusively in anchialine caves throughout the globe in a seemingly disjunct range of locations such as the Western Atlantic and Caribbean (Bahamas, Belize, Cuba, Dominican Republic, Yucatan), Africa (Canary Islands), and Western Australia (Sket, 1996;Yager & Humphreys, 1996;Koenemann et al, 2003Koenemann et al, , 2004Koenemann et al, , 2007aKoenemann et al, , 2007cKoenemann et al, , 2009aLorentzen et al, 2007;Daenekas et al, 2009;Neiber et al, 2011Neiber et al, , 2012Hoenemann et al, 2013;Koenemann & Iliffe, 2013). Although at first sight remipedes may appear morphologically primitive (Yager, 1994), they possess an advanced nervous system (Stemme et al, 2013), highly specialized feeding mouthparts for capturing prey (von Reumont et al, 2014), and they are the top predatory crustaceans in the low-oxygen anchialine systems they inhabit (Koenemann et al, 2007c;.…”
Section: Order Nectiopoda (Class Remipedia)mentioning
confidence: 84%